USTADZ AS MARRIAGE GUARDIAN FOR A MUSLIM CONVERT BRIDE - Perwitiningsih, Perwitiningsih (Awang Long Law Review, 2025)
One of the legal requirements for marriage in Islam is the presence of a guardian for the bride, including for a bride who is a convert. One of the conditions for someone to act as a guardian in a Muslim marriage is that they must be a Muslim. If the bride’s guardian by liniage does not meet the requirements to be a marriage guardian due to being a non-Muslim, the authority to officiate the marriage is transferred to the Authoritative guardian. This research is a normative legal study using a statutory approach, examining the role of an ustadz as the Authoritative guardian for a converted bride. The results of the research show that the appointment of Ustadz Yahya M.Y. as the Authoritative guardian for Mahalini did not comply with the procedures and regulations in force in Indonesia. The person who should have acted as the Authoritative guardian in the marriage of Mahalini and Rizky is the Head of the District Religious Affairs Office, who is appointed by the Minister of Religious Affairs to act as the guardian for a bride who has no lawful guardian or whose guardian does not meet the legal requirements. An invalid guardian causes marriage to be invalid as well. However, regarding the status of the child conceived by Mahalini at the time of the remarriage, based on Article 42 of the Marriage Law in conjunction with Article 99 point (a) of the Compilation of Islamic Law, the child is considered legitimate, as a child born from a valid marriage is recognized as a legitimate child and entitled to legal rights under the law.